Power characteristics in senior basketball players - competitive-level differences - Markovic, S.; Cuk, I.; Radonjic, V.; Momcilovic, V. (Facta Universitatis: Series Physical Education and Sport, 2021)
The explosive power of the lower limbs is considered to be one of the most dominant factors in modern basketball. Based on that, we assumed that power characteristics are the factor that distinguishes basketball players of different quality levels. To set qualitative levels, we tested three teams of basketball players (a total of 39 players), each participating in a competition at a different rank, from the highest national (Elite), through second national (sub-elite) to the regional (Amateur) level. Each player completed three parts of testing: jumping tests, sprint tests and isoinertial power tests. Despite the obviously better results of the elite group in the sprint variables compared to the other two groups, statistically significant differences were observed only in tests in which maximal speed (10mF and 20m) was achieved (Elite vs. Amateur, p<0.05). In three jumping tests (SJ, CMJa and RJ) we obtained significantly better results in Elite players compared to the other groups (SJ: p<0.01; CMJa: Elite vs. Sub-elite p<0.05, Elite vs. Amateur p<0.01; RJ: p<0.01), while in CMJ only a difference between the Elite and Amateur group was observed (p<0.05). In isoinertial power tests, the only difference was obtained for knee extensor muscles (Elite vs. Amateur p<0.05). In accordance with the results, it can be confirmed that power is a crucial factor in basketball performance and should be a key element in the selection of young basketball players.